Does Cementing Influence CRP and ESR Levels after Total Hip Replacement in Early Postoperative Period? A Prospective Interventional Study - Anant Krishna; Vivek Vijayakumar; Tungish Bansal; Sudhir Kumar Garg; Sandeep Gupta; Gunjar Jain (Journal of Clinical and Diagnostic Research, 2022)
Introduction: The role of C-Reactive Protein (CRP) and Erythrocyte Sedimentation Rate (ESR) in diagnosing delayed (>6 weeks) periprosthetic joint infection prior to performing a revision joint arthroplasty is well established. Aim: To evaluate the effect of bone cement on C-Reactive Protein (CRP) and Erythrocyte Sedimentation Rate (ESR) in the first 3 weeks after Total Hip Replacement (THR). Materials and Methods: This prospective interventional study was conducted in Department of Orthopaedics at Government Medical College, Chandigarh, India, between June 2014 to December 2017. Sixteen patients who underwent an uncemented THR and 15 patients who underwent a hybrid THR were included in the study. Serum CRP and ESR were measured on the day before surgery and postoperatively on days 1, 2, 3, 7, 12, and at 3 weeks. Comparison of ESR and CRP values between the groups were performed using a Student’s t-test. A p-value <0.05 was considered statistically significant. Results: There was no significant difference between the two groups with respect to age, gender, indication of surgery, comorbidities, operative time and blood loss. CRP showed a peak at day two with a mean value of 203.74±46.15 mg/L in the uncemented group and a mean of 206.10±46.78 mg/L in the hybrid group, with normalisation by 3 weeks. ESR values showed a peak on day three with a mean of 94.28±5.97 mm/hour in the uncemented group and 92.15±6.86 mm/hour in the hybrid group and remained elevated even at 3 weeks. Statistically, no significant difference was observed in CRP and ESR values after the usage of cement in total hip arthroplasty (p-value >0.05 in all cases). Conclusion: Bone cement does not affect CRP or ESR values significantly in the early phase after uncomplicated total hip arthroplasty.